Tinjauan Hukum Tentang Pertimbangan Hakim Dalam Penjatuhan Pidana Bersyarat - Enny Sumarlin (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Conditional punishment is regulated in Article 14a to Article 14f of the Criminal Code. The emergence of this conditional sentence is a reaction to public dissatisfaction with the crime of deprivation of liberty, especially the crime of deprivation of liberty, namely imprisonment, which in this case is very detrimental to both the perpetrators of the crime. The implementation of conditional punishment must meet the general requirements and special conditions. The purpose of implementing conditional sentences is to improve himself outside prison so that it will not create the stigma that the prisoner is a bad person and likes to commit crimes in the public's opinion. In a decision that imposes a prison sentence of not more than one year, the basis or reason for imposing a conditional sentence is to improve the convict's self so that he can be developed even better and avoid a bad environment, as well as educate good social attitudes and society.